PEMBELAJARAN MEMBATIK DI SMK NEGERI 2 TEGALSARI BANYUWANGI - Nabilatul Warda; Luh Suartini; Agus Sudarmawan (Jurnal Pendidikan Seni Rupa Undiksha, 2022)
This study aims to (1) describe the approach strategy applied by the teacher in learning batik at SMK Negeri 2 Tegalsari (2) describe and determine the learning method applied by the batik learning teacher (3) find out the evaluation strategy of batik learning at SMK Negeri 2 Tegalsari. The results of this study indicate (1) the learning approach used by the teacher at the time of learning to make batik by paying attention to the accuracy of the choice of approach with the condition of the students at SMK Negeri 2 Tegalsari. (2) the learning method applied by the teacher to present learning materials for class XI KKBT batik at SMK Negeri 2 Tegalsari. (3) the evaluation strategy applied to batik learning includes aspects of attitude, knowledge and skills as well as an evaluation strategy through reporting based on the curriculum applied at SMK Negeri 2 Tegalsari. This research is important to be studied as a process of developing learning strategies. The importance of this research is to reveal more about the analysis of batik learning strategies at SMK Negeri 2 Tegalsari. Keywords: Learning, Batik, SMK Negeri 2 Tegalsari.